Bactericidal effect of silver-reinforced carbon nanotube and hydroxyapatite composites. (May 2013) - Afzal, Mohammad Atif Faiz; Kalmodia, Sushma; Kesarwani, Pallavi; Basu, Bikramjit; Balani, Kantesh
Bacterial infection remains an important risk factor after orthopedic surgery. The present paper reports the synthesis of hydroxyapatite-silver (HA-Ag) and carbon nanotube-silver (CNT-Ag) composites via spark plasma sintering (SPS) route. The retention of the initial phases after SPS was confirmed by phase analysis using X-ray diffraction and Raman spectroscopy. Energy dispersive spectrum analysis showed that Ag was distributed uniformly in the CNT/HA matrix. The breakage of CNTs into spheroid particles at higher temperatures (1700℃) is attributed to the Rayleigh instability criterion. Mechanical properties (hardness and elastic modulus) of the samples were evaluated using nanoindentation testing. Ag reinforcement resulted in the enhancement of hardness (by ∼15%) and elastic modulus (∼5%) of HA samples, whereas Ag reinforcement in CNT, Ag addition does not have much effect on hardness (0.3 GPa) and elastic modulus (5 GPa). The antibacterial tests performed using Escherichia coli and Staphylococcus epidermidis s howed significant decrease (by ∼65–86%) in the number of adhered bacteria in HA/CNT composites reinforced with 5% Ag nanoparticles. Thus, Ag-reinforced HA/CNT can serve as potential antibacterial biocomposites.